2009
DOI: 10.1111/j.1439-0310.2009.01624.x
|View full text |Cite
|
Sign up to set email alerts
|

Social Networks and the Formation and Maintenance of River Otter Groups

Abstract: Many studies have evaluated why male mammals form social groups; few however have investigated how these groups are formed and maintained. We observed behavioral interactions of 15 male river otters (Lontra canadensis) captured in Prince William Sound (PWS), Alaska, and held in captivity for 10 mo. Because the otters were captured in various areas and differed in age and relatedness, we were able to test how kinship and age influenced social interactions. We also explored how kinship, age and social interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 58 publications
(193 reference statements)
1
24
0
Order By: Relevance
“…Social networks have proved to reveal valuable information on the mechanisms and functions of group living in animal species [40][41][42][43], on the spread of diseases or behavioral innovations [44][45][46][47], as well as on dispersal [48]. For our study population, social network visualization revealed structuring in eleven or twelve social groups ( Fig.…”
Section: Social Behavior Revealed By the Use Of Nest Boxesmentioning
confidence: 92%
“…Social networks have proved to reveal valuable information on the mechanisms and functions of group living in animal species [40][41][42][43], on the spread of diseases or behavioral innovations [44][45][46][47], as well as on dispersal [48]. For our study population, social network visualization revealed structuring in eleven or twelve social groups ( Fig.…”
Section: Social Behavior Revealed By the Use Of Nest Boxesmentioning
confidence: 92%
“…Although the animals were held in a captive facility rather than in a natural habit, there was some similarity in the behaviors observed in these studies. Rostain et al (2004) observed sniffing, grooming, wrestling, and scent marking, and Hansen et al (2009) observed grooming, wrestling, and mounting. The description of defecation provided by Rostain et al (2004) suggests defecation often is associated with a ''raise and flicking of the tail''.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that solitary animals do not wrestle, and if we limit the observations to social behaviors (i.e., allogroom, wrestle, mount), wrestling comprised 44.4 % of social observations. Wrestling has been observed among captive, wild-caught otters (Hansen et al 2009); this behavior was specifically described as play by Rostain et al (2004), given the lack of aggression. Allogrooming, social behavior also observed in latrines, was observed for the same otters (Rostain et al 2004;Hansen et al 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations